The Role of Spiritual Guidance Conducted by Religious Organizations in Shaping Self-Control (A Study on Inmates of Class IIB Kabanjahe Detention Center) - Julpitra Tarigan; Abdul Razak Nasution; T. Riza Zarzani (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This study aims to examine the role of spiritual guidance provided by Religious Organizations in developing self-control among correctional inmates at the Class II B Kabanjahe State Detention Center. This study uses a qualitative method with data collection techniques through interviews and observations. The results of the study reveal that the spiritual guidance activities carried out by religious organizations play a significant role in shaping the inmates' self-control abilities. Spiritual guidance can help inmates understand and accept themselves, as well as enhance their awareness and ability to exercise self-control. Therefore, this study recommends that Religious Organizations continue to provide spiritual guidance for inmates at the Class II B Kabanjahe Detention Center.